A multi-metal element in-situ doped sodium iron sulfate positive electrode material prepared by by-product sulfate and method thereof and sodium ion battery
By mixing solid waste sodium sulfate and by-product ferrous sulfate, a polymetallic element in situ doped sodium ferrous sulfate positive electrode material is prepared, which solves the problem of insufficient electrical performance in the prior art and realizes efficient and low-cost preparation of sodium ion battery materials.
Patent Information
- Application Number
- CN202411730732.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-11-29
AI Technical Summary
The prior art is difficult to effectively utilize solid waste by-products to prepare high value-added sodium ion battery materials, and the existing materials have insufficient electrical properties and cannot meet technical needs.
By mixing solid waste sodium sulfate and by-product ferrous sulfate, spray drying and sintering, a polymetallic element in situ doped sodium ferrous sulfate positive electrode material is prepared, and carbon coating is used for carbonization to improve the conductivity and electrochemical properties of the material.
It realizes high-value recycling of by-product sulfates, reduces raw material costs, improves the conductivity and electrochemical properties of the materials, and is suitable for large-scale continuous production.
Smart Images

Figure CN119219066B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sodium ion batteries, and mainly relates to a multi-metal element in-situ doped sodium iron sulfate positive electrode material prepared by by-product sulfate, a method thereof, and a sodium ion battery. Background Art
[0002] Under the background of rapid development of green economy and new energy industry, the recycling of solid waste byproducts to prepare high value-added battery materials has important social value and great economic benefits. At present, ternary precursors are the core raw materials for the preparation of ternary positive electrode materials. According to data released by Shanghai Nonferrous Metals Network, my country will produce 814,000 tons of ternary precursors in 2023. Every ton of ternary precursors will be accompanied by about 10 tons of by-product sodium salt solution, which contains a small amount of valuable metal elements such as Ni, Co, and Mn. As of 2023, the comprehensive output of my country's titanium dioxide industry has reached 4.16 million tons, with a market size of about 43.2 billion yuan. For every ton of titanium dioxide produced by the sulfuric acid method, 3.5 to 4 tons of ferrous sulfate by-product will be produced, which contains a small amount of Mg, Al, and Ti elements. Opening up a new way to utilize by-product sodium salts and iron salts: preparing sodium iron sulfate positive electrode materials for sodium ion batteries can not only cope with the challenges of environmental pollution brought about by the rapid development of social economy, but also realize the preparation of ultra-low-cost energy storage battery materials.
[0003] At present, in order to make better use of recycled products and by-products, the main research work is to improve the purity of recycled products. In order to solve the adverse effects of metal ion impurities on sodium battery raw materials, the ternary positive electrode materials with iron, cobalt and nickel are disassembled, acid-leached, and then precipitated with sodium hydroxide and ammonia water. Finally, the trace nickel, cobalt and manganese ions are removed by electrochemical deposition to obtain sodium sulfate solution, which can be used as raw materials for battery materials. The recycling process is complicated and consumes a lot of resources. At the same time, there are also related studies that use by-products or recycled products directly as battery raw materials, but the electrical properties of the battery materials obtained are poor and cannot meet the current technical requirements. Summary of the invention
[0004] In order to realize resource recycling and overcome the bottleneck of existing material development, the present invention provides a method for preparing a multi-metal element in-situ doped composite sodium ferric sulfate positive electrode material using solid waste sodium sulfate and by-product ferrous sulfate. The by-product is recycled and reused as a sulfate raw material to achieve ultra-low production and processing costs, and multi-metal elements are in-situ entropy doped to change the problem of poor intrinsic electronic conductivity caused by the MO covalent characteristics inside the material from a microscopic perspective. At the same time, the sodium ferric sulfate material is coated with different types of carbon to prepare an ultra-low-cost and good electrochemical performance sodium ferric sulfate positive electrode material.
[0005] In an embodiment of the present invention, the present invention provides a method for preparing a multi-metal element in-situ doped sodium iron sulfate positive electrode material with by-product sulfate, the method comprising the following steps:
[0006] S1. Mix solid waste sodium sulfate, anhydrous sodium sulfate, by-product ferrous sulfate and ferrous sulfate heptahydrate, add deionized water, stir to dissolve, and filter to separate the insoluble matter to obtain a sodium ferric sulfate precursor solution;
[0007] S2, stirring and mixing the sodium ferric sulfate precursor solution with an organic carbon source and an inorganic carbon source, and then spray drying to obtain a multi-metal element in-situ doped sodium ferric sulfate positive electrode material precursor;
[0008] S3, sintering the multi-metal element in-situ doped sodium iron sulfate positive electrode material precursor in an inert atmosphere to obtain the multi-metal element in-situ doped sodium iron sulfate positive electrode material;
[0009] The chemical formula of the multi-metal element in-situ doped sodium iron sulfate positive electrode material is: Na 6-2x-2y Fe x M y (SO4)3@OC@IC, where OC and IC represent organic carbon and inorganic carbon respectively, and M represents a combination of various metal elements among the impurity metal elements Ni, Mn, Co, Mg, Ti, and Al, where 0≤y≤0.3 and 1.5≤x+y≤2.
[0010] In an optional embodiment, the solid waste sodium sulfate is any one of the solid waste sodium sulfate produced by a ternary precursor and the solid waste sodium sulfate recovered from lithium iron phosphate, the purity of the sodium sulfate is 85%~90%, and the content of Ni, Co, and Mn elements is 3%~5%; the molar ratio of the solid waste sodium sulfate to anhydrous sodium sulfate is 2:1~4:1.
[0011] In an optional embodiment, the by-product ferrous sulfate is one or both of a titanium dioxide by-product and an iron tailings slag by-product, and the purity of the ferrous sulfate in the by-product ferrous sulfate is 90%~95%; wherein the content of Mg, Al and Ti elements is 2%~4%, and the molar ratio of the by-product ferrous sulfate to ferrous sulfate heptahydrate is 1.5:1~3:1.
[0012] In an optional embodiment, the concentration of the sodium iron sulfate precursor solution is 0.1~1.0 mol / L.
[0013] In an optional embodiment, the organic carbon source is one or more of ascorbic acid, citric acid, tannic acid, and acetic acid; the inorganic carbon source is one or more of aqueous carbon quantum dot slurry, aqueous carbon nanotube slurry, aqueous graphene slurry, and aqueous graphene and carbon nanotube mixed slurry; wherein the solid content of the slurry is 3~10%; and the mass ratio of the organic carbon source to the inorganic carbon source is 0.5~1:1.
[0014] In an optional embodiment, the process parameters of the spray drying process are: the induced draft fan frequency is 20-40 Hz, the feed frequency is 5-20 Hz, the inlet air temperature is 200-250°C, and the outlet air temperature is 110-130°C.
[0015] In an optional embodiment, the sintering process in step S3 is: in an inert atmosphere, heating the temperature from room temperature to 300-450° C. at a heating rate of 1-5° C. / min and sintering for 6-24 hours.
[0016] The present invention also provides a multi-metal element in-situ doped sodium ferric sulfate positive electrode material prepared by the above preparation method. The multi-metal element in-situ doped sodium ferric sulfate positive electrode material is a hollow microsphere with a particle size of 5 to 20 μm.
[0017] As the same inventive concept, an embodiment of the present invention further provides a sodium ion battery, wherein the positive electrode material of the sodium ion battery is an in-situ doped sodium iron sulfate positive electrode material with the above-mentioned multi-metal elements.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] On the one hand, the present invention provides a method for high value and recycling of by-product sodium sulfate and by-product ferrous sulfate, which greatly reduces the cost of raw materials; in addition, by controlling the raw material composition and regulating the in-situ doping of transition metal elements, the problem of low electronic conductivity of the sodium ferric sulfate positive electrode material itself is solved. Secondly, an organic carbon source is used as a reducing agent and an inorganic carbon source is used as a conductive agent to minimize the cost of sodium ferric sulfate raw materials for sodium ion batteries, solve the problem of high inorganic carbon source cost ratio and enhance the conductivity of the material at the same time, and the use of organic acids provides good reducibility and acidic environment, so that the trivalent iron, manganese and other elements in the sodium ferric sulfate precursor solution prepared by the by-product are converted into low-valent states and stably exist. The specific process includes the steps of preparation of by-product sulfate solution, filtration separation, spray drying and sintering, with ultra-low raw material cost, simple synthesis method and short production cycle, which is suitable for large-scale continuous production. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0021] Figure 1 This is a SEM-EDS image of a multi-metal element in-situ doped sodium iron sulfate positive electrode material prepared from by-product sulfate prepared in Example 1 of the present invention;
[0022] Figure 2 X-ray diffraction patterns (XRD) of the multi-metal element in-situ doped sodium ferric sulfate positive electrode material prepared by the by-product sulfate prepared in Example 1 of the present invention and the carbon composite sodium ferric sulfate positive electrode material prepared in Comparative Example 1;
[0023] Figure 3 Raman analysis spectra of the multi-metal element in-situ doped sodium iron sulfate positive electrode material prepared from by-product sulfate prepared in Example 1 of the present invention and the positive electrode material prepared in Comparative Example 2; (a) is Example 1, (b) is Comparative Example 2;
[0024] Figure 4 The first cycle charge and discharge curve of the button cell assembled with the multi-metal element in-situ doped sodium iron sulfate positive electrode material prepared by the by-product sulfate prepared in Example 1 of the present invention and the positive electrode material of Comparative Example 1 at a current rate of 0.1C at a voltage of 2-4.5V;
[0025] Figure 5 Cycling curves of button cells assembled with the multi-metal element in-situ doped sodium iron sulfate positive electrode material prepared with by-product sulfate prepared in Example 1 of the present invention and the positive electrode material of Comparative Example 1 at a voltage of 2-4.5V and a 1C rate. DETAILED DESCRIPTION
[0026] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the present invention, but the protection scope of the present invention is not limited to the following specific embodiments.
[0027] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.
[0028] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0029] Sodium iron sulfate is a commonly used sodium ion battery material. Its main raw materials are anhydrous sodium sulfate and ferrous sulfate heptahydrate. The raw material costs are as follows:
[0030] Table 1 Comparison of the cost price of different sodium iron sulfate materials
[0031]
[0032] As can be seen from the above table, the cost of using high-purity anhydrous sodium sulfate and ferrous sulfate heptahydrate is much higher than that of solid waste sodium sulfate and byproduct ferrous sulfate. In order to recycle the above solid waste and byproducts at a high value and ensure the electrical properties of sodium ferric sulfate positive electrode materials, an embodiment of the present invention provides a method for preparing a multi-metal element in-situ doped sodium ferric sulfate positive electrode material using byproduct sulfate, comprising the following steps:
[0033] After preliminarily mixing solid waste sodium sulfate and anhydrous sodium sulfate, ferrous sulfate heptahydrate and titanium dioxide by-product ferrous sulfate in a certain proportion, they are added to a reaction device filled with deionized water in turn and stirred thoroughly. After the sodium sulfate and ferrous sulfate are fully dissolved, the insoluble matter is filtered to separate the sodium ferric sulfate precursor solution; wherein the solid waste sodium sulfate is any one of the solid waste sodium sulfate produced by the ternary precursor and the solid waste sodium sulfate recovered from lithium iron phosphate, the purity of the sodium sulfate is 85%~90%, wherein the Ni, Co, and Mn element contents are 3%~5%; the molar ratio of solid waste sodium sulfate to anhydrous sodium sulfate is 2:1~4:1; the by-product ferrous sulfate is one or two of the titanium dioxide by-product and the iron tailings slag by-product, and the purity of the ferrous sulfate in the by-product ferrous sulfate is 90%~95%; wherein the Mg, Al, and Ti element contents are 2%~4%, and the molar ratio of the by-product ferrous sulfate to ferrous sulfate heptahydrate is 1.5:1~3:1. Preferably, the concentration of sodium sulfate in the precursor solution is controlled to be 0.5-1.0 mol / L; the concentration of ferrous sulfate is 0.5-1.0 mol / L, and the molar ratio of sodium sulfate to ferrous sulfate is (0.5-1.0): 1. The concentration of the sodium ferric sulfate precursor solution is 0.1-1 mol / L, more preferably 0.5 mol / L.
[0034] After the sodium ferric sulfate precursor solution is stirred and mixed with an organic carbon source and an inorganic carbon source, spray drying is performed to obtain a multi-metal element in-situ doped sodium ferric sulfate positive electrode material precursor. In this process, the organic carbon source is one or more of ascorbic acid, citric acid, tannic acid, and acetic acid and the purity is analytically pure, and ascorbic acid is more preferred. The mass ratio of the amount of the added organic carbon source to the sodium ferric sulfate is 0.001~0.02:1. Too much addition of the organic carbon source will reduce the proportion of active substances in the material system, resulting in a decrease in the conductivity of the material, and the electrochemical performance cannot be effectively exerted. The inorganic carbon source is one or more of an aqueous carbon quantum dot slurry, an aqueous carbon nanotube slurry, an aqueous graphene slurry, and an aqueous graphene and carbon nanotube mixed slurry; the slurry solid content is 3~10%, and more preferably 5%. Regarding the selection of inorganic carbon sources, when the solid content is too high, the consistency and stability of the slurry will be poor, and it will easily agglomerate into a gel-like state, which is not conducive to long-term use, and the cost of raw materials will increase; if the solid content is too low, the solid content of the entire system will be reduced, affecting the particle size and conductivity of the material, and reducing the electrochemical properties of the material. In addition, the mass ratio of the amount of inorganic carbon source added to sodium iron sulfate is 0.01~0.05:1. Too much inorganic carbon source addition will reduce the proportion of active substances in the material system and increase the cost of material production. If the addition amount is too low, the material conductivity is poor, and the electrochemical performance cannot be effectively exerted. In the spray drying process of this step, the induced draft fan frequency of the spray drying equipment is 20~40Hz, more preferably 30Hz; the inlet air temperature is 200~250℃, more preferably 225℃; the outlet air temperature is 110~130℃, more preferably 120℃.
[0035] The above precursor is sintered in an inert atmosphere to obtain a sodium iron sulfate positive electrode material in situ doped with multiple metal elements. During calcination, first ventilate for 120 minutes under the protection of a protective atmosphere such as nitrogen, argon or an inert mixed gas, then heat from room temperature to 300~450°C at a heating rate of 1~5°C / min, and calcine for 6-24 hours. More preferably, the temperature is raised to 350°C at 5°C / min and calcined for 10 hours. Through one-step calcination, the sodium iron sulfate precursor can remove crystal water and form a spherical sodium iron sulfate positive electrode material with a good crystal structure. The above sintering temperature is too high, which will cause the sulfate ions in the sodium iron sulfate to decompose and Fe 2+ It turns into iron oxide compounds, resulting in a decrease in the content of metal ions involved in redox in the material, and a decrease in specific capacity and cycle performance; if the sintering temperature is too low, the crystal water in the precursor material will not be separated, and a nucleophilic reaction will occur with the electrolyte, resulting in a decrease in the first coulombic efficiency of the material; at the same time, the material has a low degree of crystallinity, resulting in the coexistence of impurities with low electrochemical activity, which leads to poor electrochemical performance of the material.
[0036] The present invention simultaneously uses two solid waste by-product sulfates as ultra-low-cost raw materials, achieving recycling and high added value utilization, simple operation and efficient utilization. Secondly, the in-situ doping of transition metal elements is regulated to solve the problem of low intrinsic electronic conductivity from the internal structure of the material. Finally, the addition of an organic carbon source provides a reducing and acidic environment for the precursor solution, so that the electrochemically inactive trivalent iron, manganese and other elements in the precursor solution are converted into a divalent state and exist stably, thereby effectively improving the utilization rate of by-product materials. The sodium ferric sulfate precursor with controllable morphology and uniform mixing of raw materials at the atomic level is prepared by spray drying. After low-temperature calcination, a composite sodium ferric sulfate positive electrode material prepared by in-situ doping of multiple metal elements using by-product sulfate is successfully synthesized.
[0037] The chemical formula of the multi-metal element in-situ doped sodium iron sulfate positive electrode material prepared by the above method is: Na 6-2x-2y Fe x M y (SO4)3@OC@IC, where OC and IC represent organic carbon and inorganic carbon respectively, and M represents a combination of multiple metal elements among the impurity metal elements Ni, Mn, Co, Mg, Ti, and Al, where 0≤y≤0.3, 1.5≤x+y≤2; the multi-metal element in-situ doped sodium iron sulfate positive electrode material is a hollow microsphere with a particle size of 5~20μm. The positive electrode material can be used as a sodium ion battery material in sodium ion batteries to prepare a new type of sodium ion battery.
[0038] The above introduces the specific implementation methods of the present application. In order to objectively illustrate the technical effects produced by the present application, the following examples and comparative examples will be used for description.
[0039] The solid waste sodium sulfate associated with the ternary precursor used in the present invention comes from Zhongwei New Materials Co., Ltd.; the by-product ferrous sulfate of titanium dioxide comes from Chongqing Xiatung New Energy Materials Co., Ltd.
[0040] Example 1
[0041] A method for in-situ doping of sodium iron sulfate positive electrode material with multi-metal elements prepared by by-product sulfate comprises the following steps:
[0042] First, a ternary precursor with a molar ratio of 2.5:1 is used to produce solid waste sodium sulfate (with a purity of 90%, chemical titration test) and analytical pure sodium sulfate reagent. After mixing, the sodium sulfate content is 92%~95%, of which the Ni, Co, and Mn elements are 0.1%~5%, and then added to deionized water. Secondly, a titanium dioxide byproduct ferrous sulfate heptahydrate (with a purity of 90%, chemical titration test) and analytical pure ferrous sulfate heptahydrate reagent with a molar ratio of 1.7:1 are taken. After mixing, the ferrous sulfate content is 92%~98%, of which the Mg element content is 0.1%~3%, and dissolved in deionized water. The molar ratio of sodium and iron ions in the precursor solution is controlled to be 1.5:1. The reactor is kept stirred continuously during the entire feeding process, with a speed of 500rpm and a stirring time of 20min, until the sodium sulfate and ferrous sulfate reagents are fully dissolved in water. Filter and separate the excess insoluble matter to obtain a 0.5mol / L sodium iron sulfate precursor solution.
[0043] First, ascorbic acid was added to the above precursor solution at a ratio of 1wt% of organic carbon content to sodium iron sulfate; secondly, an aqueous carbon nanotube slurry with a solid content of 5% was added to the above precursor solution at a ratio of 2wt% of inorganic carbon content to sodium iron sulfate, and added to the reaction stirring kettle, maintained at a constant temperature of 30°C, a rotation speed of 700rpm, and stirred for 20min. Spray drying was used to obtain the inorganic carbon composite sodium iron sulfate positive electrode material precursor Na 2.56 Fe 1.7 (MgNiMnCo) 0.02 (SO4)3·xH2O / Vc / CNTs (x=2, 4). The inlet air temperature of the spray drying is 225°C, the outlet air temperature is 120°C, the feed frequency is 10Hz, the induced draft fan frequency is 30Hz, and the precursor solution is continuously stirred while feeding, with a stirring speed of 450rpm.
[0044] The multi-metal element in-situ doped sodium ferric sulfate positive electrode material precursor obtained above was ventilated in a nitrogen atmosphere at room temperature for 2 hours to ensure that the tubular furnace was filled with nitrogen and other gas components; then, under the protection of the nitrogen atmosphere, the temperature was raised from room temperature to 380°C at a heating rate of 5°C / min and calcined for 10 hours to obtain a multi-metal element in-situ doped sodium ferric sulfate positive electrode material prepared using solid waste sodium sulfate and by-product ferrous sulfate.
[0045] Example 2
[0046] A method for in-situ doping of sodium iron sulfate positive electrode materials with multi-metal elements prepared by by-product sulfate comprises the following steps:
[0047] First, a ternary precursor with a molar ratio of 3:1 is used to produce solid waste sodium sulfate (with a purity of 85%, chemical titration test) and analytical pure sodium sulfate reagent. After mixing, the sodium sulfate content is 90%~93%, of which the Ni, Co, and Mn elements are 0.1%~7%, and then added to deionized water. Secondly, a titanium dioxide byproduct ferrous sulfate heptahydrate (with a purity of 88%, chemical titration test) and analytical pure ferrous sulfate heptahydrate reagent with a molar ratio of 2.5:1 are taken. After mixing, the ferrous sulfate content is 90%~95%, of which the Mg and Ti elements are 0.1%~5%, and dissolved in deionized water. The molar ratio of sodium and iron ions in the precursor solution is controlled to be 1.4:1. The reactor is kept stirred continuously during the entire feeding process, with a speed of 500rpm and a stirring time of 20min, until the sodium sulfate and ferrous sulfate reagents are fully dissolved in water. Filter and separate the excess insoluble matter to obtain a 0.5mol / L sodium iron sulfate precursor solution.
[0048] First, ascorbic acid was added to the above precursor solution at a ratio of 1wt% of organic carbon content to sodium iron sulfate; secondly, an aqueous carbon nanotube slurry with a solid content of 5% was added to the above precursor solution at a ratio of 2wt% of inorganic carbon content to sodium iron sulfate, and added to the reaction stirring kettle, maintained at a constant temperature of 30°C, a rotation speed of 700rpm, and stirred for 20min. Spray drying was used to obtain the inorganic carbon composite sodium iron sulfate positive electrode material precursor Na 2.34 Fe 1.7 (MgNiMnCoTi) 0.13 (SO4)3·xH2O / Vc / CNTs (x=2, 4). The inlet air temperature of the spray drying is 225°C, the outlet air temperature is 120°C, the feed frequency is 10Hz, the induced draft fan frequency is 30Hz, and the precursor solution is continuously stirred while feeding, with a stirring speed of 450rpm.
[0049] The multi-metal element in-situ doped sodium ferric sulfate positive electrode material precursor obtained above was ventilated in a nitrogen atmosphere at room temperature for 2 hours to ensure that the tubular furnace was filled with nitrogen and other gas components; then, under the protection of the nitrogen atmosphere, the temperature was raised from room temperature to 380°C at a heating rate of 5°C / min and calcined for 10 hours to obtain a multi-metal element in-situ doped sodium ferric sulfate positive electrode material prepared using solid waste sodium sulfate and by-product ferrous sulfate.
[0050] Example 3
[0051] A method for in-situ doping of sodium iron sulfate positive electrode materials with multi-metal elements prepared by by-product sulfate comprises the following steps:
[0052] First, a ternary precursor with a molar ratio of 2.5:1 is used to produce solid waste sodium sulfate (with a purity of 90%, chemical titration test) and analytical pure sodium sulfate reagent. After mixing, the sodium sulfate content is 92%~95%, of which the Ni, Co, and Mn elements are 0.1%~5%, and then added to deionized water. Secondly, a titanium dioxide byproduct ferrous sulfate heptahydrate (with a purity of 90%, chemical titration test) and analytical pure ferrous sulfate heptahydrate reagent with a molar ratio of 1.7:1 are taken. After mixing, the ferrous sulfate content is 92%~98%, of which the Mg element content is 0.1%~3%, and dissolved in deionized water. The molar ratio of sodium and iron ions in the precursor solution is controlled to be 1.5:1. The reactor is kept stirred continuously during the entire feeding process, with a speed of 500rpm and a stirring time of 20min, until the sodium sulfate and ferrous sulfate reagents are fully dissolved in water. Filter and separate the excess insoluble matter to obtain a 0.5mol / L sodium iron sulfate precursor solution.
[0053] First, ascorbic acid was added to the above precursor solution at a ratio of 2wt% of organic carbon content to sodium iron sulfate; secondly, an aqueous carbon nanotube slurry with a solid content of 5% was added to the above precursor solution at a ratio of 1wt% of inorganic carbon content to sodium iron sulfate, and then added to the reaction stirring kettle, maintained at a constant temperature of 30°C, a rotation speed of 700rpm, and stirred for 20min. Spray drying was performed to obtain the inorganic carbon composite sodium iron sulfate positive electrode material precursor Na 2.56 Fe 1.7 (MgNiMnCo) 0.02 (SO4)3·xH2O / Vc / CNTs (x=2, 4). The inlet air temperature of the spray drying is 225°C, the outlet air temperature is 120°C, the feed frequency is 10Hz, the induced draft fan frequency is 30Hz, and the precursor solution is continuously stirred while feeding, with a stirring speed of 450rpm.
[0054] The multi-metal element in-situ doped sodium ferric sulfate positive electrode material precursor obtained above was ventilated in a nitrogen atmosphere at room temperature for 2 hours to ensure that the tubular furnace was filled with nitrogen and other gas components; then, under the protection of the nitrogen atmosphere, the temperature was raised from room temperature to 380°C at a heating rate of 5°C / min and calcined for 10 hours to obtain a multi-metal element in-situ doped sodium ferric sulfate positive electrode material prepared using solid waste sodium sulfate and by-product ferrous sulfate.
[0055] Example 4
[0056] A method for in-situ doping of sodium iron sulfate positive electrode materials with multi-metal elements prepared by by-product sulfate comprises the following steps:
[0057] First, a ternary precursor with a molar ratio of 2.5:1 is used to produce solid waste sodium sulfate (with a purity of 90%, chemical titration test) and analytical pure sodium sulfate reagent. After mixing, the sodium sulfate content is 92%~95%, of which the Ni, Co, and Mn elements are 0.1%~5%, and then added to deionized water. Secondly, a titanium dioxide byproduct ferrous sulfate heptahydrate (with a purity of 90%, chemical titration test) and analytical pure ferrous sulfate heptahydrate reagent with a molar ratio of 1.7:1 are taken. After mixing, the ferrous sulfate content is 92%~98%, of which the Mg element content is 0.1%~3%, and dissolved in deionized water. The molar ratio of sodium and iron ions in the precursor solution is controlled to be 1.5:1. The reactor is kept stirred continuously during the entire feeding process, with a speed of 500rpm and a stirring time of 20min, until the sodium sulfate and ferrous sulfate reagents are fully dissolved in water. Filter and separate the excess insoluble matter to obtain a 0.5mol / L sodium iron sulfate precursor solution.
[0058] First, ascorbic acid was added to the above precursor solution at a ratio of 1wt% of organic carbon content to sodium iron sulfate; secondly, an aqueous carbon nanotube slurry with a solid content of 5% was added to the above precursor solution at a ratio of 2wt% of inorganic carbon content to sodium iron sulfate, and added to the reaction stirring kettle, maintained at a constant temperature of 30°C, a rotation speed of 700rpm, and stirred for 20min. Spray drying was used to obtain the inorganic carbon composite sodium iron sulfate positive electrode material precursor Na 2.56 Fe 1.7 (MgNiMnCo) 0.02 (SO4)3·xH2O / Vc / CNTs (x=2, 4). The inlet temperature of the spray drying was 200°C, the outlet temperature was 100°C, the feed frequency was 10 Hz, the induced draft fan frequency was 30 Hz, and the precursor solution was continuously stirred while feeding, with a stirring speed of 450 rpm.
[0059] The multi-metal element in-situ doped sodium ferric sulfate positive electrode material precursor obtained above was ventilated in a nitrogen atmosphere at room temperature for 2 hours to ensure that the tubular furnace was filled with nitrogen and other gas components; then, under the protection of the nitrogen atmosphere, the temperature was raised from room temperature to 350°C at a heating rate of 5°C / min and calcined for 10 hours to obtain a multi-metal element in-situ doped sodium ferric sulfate positive electrode material prepared using solid waste sodium sulfate and by-product ferrous sulfate.
[0060] Comparative Example 1
[0061] A method for in-situ doping of sodium iron sulfate positive electrode material with multi-metal elements prepared by by-product sulfate comprises the following steps:
[0062] First, take the ternary precursor with a molar ratio of 0.78:1 to produce solid waste sodium sulfate (purity of 90%, of which Ni, Co, and Mn content are 0.1%~5%) and titanium dioxide by-product ferrous sulfate heptahydrate (purity of 90%, of which Mg and Ti content are 0.1%~3%), mix them and dissolve them in deionized water. Control the molar ratio of sodium and iron ions in the precursor solution to be 1.4:1. Keep the reactor stirring continuously during the entire feeding process, the speed is 500rpm, and the stirring time is maintained for 20min, until the sodium sulfate and ferrous sulfate reagents are fully dissolved in water. Filter and separate the excess insoluble matter to obtain a 0.5mol / L sodium iron sulfate precursor solution.
[0063] First, ascorbic acid was added to the above precursor solution at a ratio of 1wt% of organic carbon content to sodium iron sulfate; secondly, an aqueous carbon nanotube slurry with a solid content of 5% was added to the above precursor solution at a ratio of 2wt% of inorganic carbon content to sodium iron sulfate, and added to the reaction stirring kettle, maintained at a constant temperature of 30°C, a rotation speed of 700rpm, and stirred for 20min. Spray drying was used to obtain the inorganic carbon composite sodium iron sulfate positive electrode material precursor Na 2.4 Fe 1.7 (MgNiMnCo) 0.2 (SO4)3·xH2O / Vc / CNTs (x=2, 4). The inlet air temperature of the spray drying is 225°C, the outlet air temperature is 120°C, the feed frequency is 10Hz, the induced draft fan frequency is 30Hz, and the precursor solution is continuously stirred while feeding, with a stirring speed of 450rpm.
[0064] The multi-metal element in-situ doped sodium ferric sulfate positive electrode material precursor obtained above was ventilated in a nitrogen atmosphere at room temperature for 2 hours to ensure that the tubular furnace was filled with nitrogen and other gas components; then, under the protection of the nitrogen atmosphere, the temperature was raised from room temperature to 380°C at a heating rate of 5°C / min and calcined for 10 hours to obtain a multi-metal element in-situ doped sodium ferric sulfate positive electrode material prepared using solid waste sodium sulfate and by-product ferrous sulfate.
[0065] Comparative Example 2
[0066] A method for preparing sodium ferric sulfate positive electrode material from sodium sulfate and ferrous sulfate comprises the following steps:
[0067] First, take anhydrous sodium sulfate reagent and ferrous sulfate heptahydrate reagent in a molar ratio of 1:1, mix and dissolve in deionized water. Control the molar ratio of sodium and iron ions in the precursor solution to be 1.5:1. Keep the reactor stirring continuously during the entire feeding process at a speed of 500 rpm and keep stirring for 20 minutes. After the sodium sulfate and ferrous sulfate reagents are fully dissolved in water, a 0.5 mol / L sodium iron sulfate precursor solution is obtained.
[0068] First, ascorbic acid was added to the above precursor solution at a ratio of 1wt% of organic carbon content to sodium iron sulfate; secondly, an aqueous carbon nanotube slurry with a solid content of 5% was added to the above precursor solution at a ratio of 2wt% of inorganic carbon content to sodium iron sulfate, and added to the reaction stirring kettle, maintained at a constant temperature of 30°C, a rotation speed of 700rpm, and stirred for 20min. Spray drying was used to obtain the inorganic carbon composite sodium iron sulfate positive electrode material precursor Na 2.6 Fe 1.7 (SO4)3·xH2O / Vc / CNTs (x=2, 4). The inlet air temperature of the spray drying is 225°C, the outlet air temperature is 120°C, the feed frequency is 10Hz, the induced draft fan frequency is 30Hz, and the precursor solution is continuously stirred while feeding, with a stirring speed of 500rpm.
[0069] The multi-carbon composite sodium ferric sulfate positive electrode material precursor obtained above was ventilated in a nitrogen atmosphere at room temperature for 2 hours to ensure that the tubular furnace was filled with nitrogen and other gas components; then, under the protection of the nitrogen atmosphere, the temperature was raised from room temperature to 380°C at a heating rate of 5°C / min and calcined for 10 hours to obtain the sodium ferric sulfate positive electrode material.
[0070] Comparative Example 3
[0071] A method for in-situ doping of sodium iron sulfate positive electrode materials with multi-metal elements prepared by by-product sulfate comprises the following steps:
[0072] First, a ternary precursor with a molar ratio of 2.5:1 is used to produce solid waste sodium sulfate (with a purity of 90%, chemical titration test) and analytical pure sodium sulfate reagent. After mixing, the sodium sulfate content is 92%~95%, of which the Ni, Co, and Mn elements are 0.1%~5%, and then added to deionized water. Secondly, a titanium dioxide byproduct ferrous sulfate heptahydrate (with a purity of 90%, chemical titration test) and analytical pure ferrous sulfate heptahydrate reagent with a molar ratio of 1.7:1 are taken. After mixing, the ferrous sulfate content is 92%~98%, of which the Mg element content is 0.1%~3%, and dissolved in deionized water. The molar ratio of sodium and iron ions in the precursor solution is controlled to be 1.5:1. The reactor is kept stirred continuously during the entire feeding process, with a speed of 500rpm and a stirring time of 20min, until the sodium sulfate and ferrous sulfate reagents are fully dissolved in water. Filter and separate the excess insoluble matter to obtain a 0.5mol / L sodium iron sulfate precursor solution.
[0073] According to the ratio of inorganic carbon content to sodium iron sulfate 1wt%, add 5% solid content of water-based carbon nanotube slurry to the above precursor solution, add it to the reaction stirring kettle, keep the constant temperature at 30°C, the speed at 700rpm, and stir for 20min. Spray drying is used to obtain the inorganic carbon composite sodium iron sulfate positive electrode material precursor Na 2.56 Fe1.7 (MgNiMnCo) 0.02 (SO4)3·xH2O / Vc / CNTs (x=2, 4). The inlet air temperature of the spray drying is 225°C, the outlet air temperature is 120°C, the feed frequency is 10Hz, the induced draft fan frequency is 30Hz, and the precursor solution is continuously stirred while feeding, with a stirring speed of 450rpm.
[0074] The multi-metal element in-situ doped sodium ferric sulfate positive electrode material precursor obtained above was ventilated in a nitrogen atmosphere at room temperature for 2 hours to ensure that the tubular furnace was filled with nitrogen and other gas components; then, under the protection of the nitrogen atmosphere, the temperature was raised from room temperature to 380°C at a heating rate of 5°C / min and calcined for 10 hours to obtain a multi-metal element in-situ doped sodium ferric sulfate positive electrode material prepared using solid waste sodium sulfate and by-product ferrous sulfate.
[0075] Performance Testing
[0076] The positive electrode materials obtained in the above examples and comparative examples were subjected to scanning electron microscopy, X-ray diffraction analysis and ex situ Raman analysis to obtain SEM-EDS images, X-ray diffraction patterns and Raman spectra, respectively. Figure 1 The multi-metal element in-situ doped sodium ferric sulfate material prepared by solid waste sulfate and by-product ferrous sulfate presents a hollow spherical shape. At the same time, SEM-EDS shows that the material obviously contains a small amount of Ni, Mn, Co, Mg and other elements. The X-ray diffraction spectrum is as follows Figure 2 As shown in Figure 1, all the diffraction peaks of the crystal plane correspond to the standard card, proving that the sodium iron sulfate positive electrode material was successfully synthesized. Figure 3 As shown, Figures (a) and (b) correspond to the corresponding materials obtained in Example 1 and Comparative Example 3, respectively. In the Raman spectrum, it is generally believed that the smaller the peak intensity ratio of the D band to the G band, the more sp2 graphitized carbon content of the composite material after carbon coating, thereby ensuring that the material has better electronic conductivity. The peak intensity ratio of the D band to the G band in Comparative Example 3 is 0.901, while the peak intensity ratio of the D band to the G band in Example 1 is 0.355, indicating that the sp2 carbon content of the material is relatively higher and the electronic conductivity of the material is higher.
[0077] Application of cathode materials
[0078] The positive electrode materials obtained in the above-mentioned embodiments and comparative examples were assembled into batteries: Under the condition of a dew point below -30°C, 0.0800g of the sodium iron sulfate positive electrode material obtained in this embodiment or comparative example was weighed, 0.0100g of conductive carbon black as a conductive agent and 0.0100g of PVDF (polyvinylidene fluoride) as a binder were added, mixed evenly and coated on aluminum foil to make a positive electrode sheet, and in a vacuum glove box, a metal sodium sheet was used as the negative electrode, the battery separator was a Whatman GF / D glass fiber separator, and the electrolyte was 1mol / LNaClO4 (EC:DMC=1:1 (vol%) +5%FEC), and assembled into a CR2032 button battery. Electrochemical performance tests and cycle performance tests were carried out in the range of 2~4.5V, specifically testing the first discharge capacity at 0.1C, the first coulomb efficiency, the discharge specific capacity at a current rate of 1C, and the capacity retention rate after 100 cycles. For specific results, see Figure 4 , 5 and Table 2.
[0079] Table 2 Electrical properties and cycle performance test results
[0080]
[0081] In comparative example 1, the introduction of more impurity metal ions occupied the sodium position, reducing the Na + At the same time, metal ions enter the lattice to change the material phase composition, hindering the migration of sodium ions, resulting in the inability to fully utilize the material capacity. Compared with Comparative Example 2, Example 1, on the one hand, broadens the Na content of the material by doping with a certain amount of metal elements. + migration channel, effectively improving the discharge capacity of the material; on the other hand, the entropy doping of nickel, cobalt, manganese and other elements in the by-product is used to change the Fe-O bond characteristics, so that the intrinsic electronic conductivity of the material is improved. 3+ , Fe 3+ Electrochemically inactive metal ions enter the material lattice and occupy the Fe 2+ sites but cannot participate in redox reactions, which ultimately leads to the degradation of the electrochemical performance of the material.
[0082] The present invention utilizes multi-metallic elements prepared by by-product sulfate to in-situ dope sodium iron sulfate positive electrode materials, thereby achieving direct and high-value utilization of sulfate by-products of a certain purity, and greatly reducing the cost of raw materials. In-situ multi-metallic element entropy doping changes the problem of poor intrinsic electronic conductivity caused by the covalent characteristics of MO inside the material from a microscopic perspective. The use of an organic carbon source can reduce trivalent iron to divalent iron and maintain its stable existence; at the same time, a dense coating conductive layer is formed during the calcination and carbonization process, which improves the electronic conductivity and air stability of the material and prevents environmental moisture from corroding the material. In the preparation process, the raw materials used are extremely easy to obtain, the processing process is relatively simple, the social benefits are good, and the economic benefits are huge.
[0083] The above contents are further detailed descriptions of the present invention in combination with specific preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, which should be regarded as falling within the scope of protection of the present invention.
Claims
1. A method for in-situ doping of sodium iron sulfate positive electrode materials with multi-metal elements prepared by by-product sulfate, characterized in that: The method comprises the following steps: S1. Mix solid waste sodium sulfate, anhydrous sodium sulfate, by-product ferrous sulfate and ferrous sulfate heptahydrate, add deionized water, stir to dissolve, and filter to separate the insoluble matter to obtain a sodium ferric sulfate precursor solution; the molar ratio of the solid waste sodium sulfate to the anhydrous sodium sulfate is 2:1-4:1, and the molar ratio of the by-product ferrous sulfate to ferrous sulfate heptahydrate is 1.5:1-3:1; the purity of sodium sulfate in the solid waste sodium sulfate is 85%-90%, wherein the content of Ni, Co and Mn elements is 3%-5%; the purity of ferrous sulfate in the by-product ferrous sulfate is 90%-95%; wherein the content of Mg, Al and Ti elements is 2%-4%; S2, stirring and mixing the sodium ferric sulfate precursor solution with an organic carbon source and an inorganic carbon source, and then spray drying to obtain a multi-metal element in-situ doped sodium ferric sulfate positive electrode material precursor; the mass ratio of the amount of the organic carbon source to the sodium ferric sulfate is 0.001-0.02:1, the mass ratio of the amount of the inorganic carbon source to the sodium ferric sulfate is 0.01-0.05:1; the mass ratio of the organic carbon source to the inorganic carbon source is 0.5-1:1; S3, sintering the multi-metal element in-situ doped sodium iron sulfate positive electrode material precursor in an inert atmosphere to obtain a multi-metal in-situ doped sodium iron sulfate positive electrode material; The chemical formula of the multi-metal element in-situ doped sodium iron sulfate positive electrode material is: Na 6-2x-2y Fe x M y (SO4)3@OC@IC, where OC and IC represent organic carbon and inorganic carbon respectively, and M represents a combination of various metal elements among the impurity metal elements Ni, Mn, Co, Mg, Ti, and Al, where 0≤y≤0.3 and 1.5≤x+y≤2.
2. The method for preparing multi-metal element in-situ doped sodium iron sulfate positive electrode material using by-product sulfate according to claim 1, characterized in that: The solid waste sodium sulfate is any one of the solid waste sodium sulfate produced by the ternary precursor and the solid waste sodium sulfate recovered from lithium iron phosphate.
3. The method for preparing a multi-metal element in-situ doped sodium iron sulfate positive electrode material using by-product sulfate according to claim 1, characterized in that: The by-product ferrous sulfate is one or both of a titanium dioxide by-product and an iron tailings slag by-product.
4. The method for preparing a multi-metal element in-situ doped sodium iron sulfate positive electrode material using by-product sulfate according to claim 1, characterized in that: The concentration of the sodium iron sulfate precursor solution is 0.1-1.0 mol / L.
5. The method for preparing multi-metal element in-situ doped sodium iron sulfate positive electrode material using by-product sulfate according to claim 1, characterized in that: The organic carbon source is one or more of ascorbic acid, citric acid, tannic acid and acetic acid.
6. The method for preparing multi-metal element in-situ doped sodium iron sulfate positive electrode material using by-product sulfate according to claim 1, characterized in that: The inorganic carbon source is one or more of water-based carbon quantum dot slurry, water-based carbon nanotube slurry, water-based graphene slurry and water-based graphene and carbon nanotube mixed slurry; wherein the solid content of the slurry is 3-10%.
7. The method for preparing multi-metal element in-situ doped sodium iron sulfate positive electrode material using by-product sulfate according to claim 1, characterized in that: The process parameters of the spray drying process are: the frequency of the induced draft fan is 20-40 Hz, the feeding frequency is 5-20 Hz, the inlet air temperature is 200-250° C., and the outlet air temperature is 110-130° C.
8. The method for preparing multi-metal element in-situ doped sodium iron sulfate positive electrode material using by-product sulfate according to claim 1, characterized in that: The sintering process in step S3 is: in an inert atmosphere, heating the temperature from room temperature to 300-450° C. at a heating rate of 1-5° C. / min for 6-24 hours.
9. A multi-metal element in-situ doped sodium iron sulfate positive electrode material obtained by the method according to any one of claims 1 to 8, characterized in that: The multi-metal element in-situ doped sodium iron sulfate positive electrode material is a hollow microsphere with a particle size of 5-20 μm.
10. A sodium ion battery, characterized in that: The positive electrode material of the sodium ion battery comprises the multi-metal element in-situ doped sodium iron sulfate positive electrode material according to claim 9.
Citation Information
Patent Citations
Composite sodium ferrous sulfate positive electrode material as well as preparation method and application thereof
CN116995227A
Method for preparing sodium ferric sulfate serving as positive electrode material of sodium-ion battery by using titanium dioxide by-product
CN117303449A
Process for recycling waste lithium battery with nickel-cobalt-manganese ternary positive electrode material
CN118771415A